Airway epithelial barrier dysfunction in the pathogenesis and prognosis of respiratory tract diseases in childhood and adulthood. Issue 4 (2nd October 2017) - Yuksel, Hasan; Turkeli, Ahmet
ABSTRACT: The lungs are in direct contact with the environment through the tubular structure that constitutes the airway. Starting from the nasal orifice, the airway is exposed to foreign particles including infectious agents, allergens, and other substances that can damage the airways. Therefore, the airway must have a functional epithelial barrier both in the upper and lower airways to protect against these threats. As with the skin, it is likely that the pathogenesis of respiratory diseases is a consequence of epithelial barrier defects in these airways. The characteristics of this system, starting from the beginning of life and extending into maturing and aging, determine the prognosis of respiratory diseases. In this article, we discuss the pathogenesis, clinical phenotype, and prognosis of respiratory diseases from newborns to adulthood in the context of epithelial barrier function and dysfunction.